Hypothetical Immunological and Immunogenetic Model of Heterogenous Effects of BCG Vaccination in SARS-CoV-2 Infections: BCG-induced Trained and Heterologous Immunity - Kovačić, Dženan; Gajić, Andrej A.; Latinović, Dado; Softić, Adna (Journal of Medical Science, 2021)
Though SARS-CoV-2 infections are yet to be completely characterised in a host-pathogen interaction context, some of the mechanisms governing the interaction between the novel betacoronavirus and the human host, have been brought to light in satisfactory detail. Among the emerging evidence, postulates regarding potential benefits of innate immune memory and heterologous immunity have been put under discussion. Innate immune memory entails epigenetic reprogramming of innate immune cells caused by vaccination or infections, whereas heterologous immunity denotes cross-reactivity of T cells with unrelated epitopes and bystander CD8+ activation. Familiarization of the host immune system with a certain pathogen, educates monocytes, macrophages and other innate cells into phenotypes competent for combating unrelated pathogens. Indeed, the resolution at which non-specific innate immune memory occurs, is predominant at the level of enhanced cytokine secretion as a result of epigenetic alterations. One vaccine whose non-specific effects have been documented and harnessed in treating infections, cancer and autoimmunity, is the Bacillus Calmette–Guérin (BCG) vaccine currently used for immunization against pulmonary tuberculosis (TB). The BCG vaccine induces a diverse cytokine secretion profile in immunized subjects, which in turn may stimulate epigenetic changes mediated by immunoreceptor signalling. Herein, we provide a concise summarization of previous findings regarding the effects of the BCG vaccine on innate immune memory and heterologous immunity, supplemented with clinical evidence of the non-specific effects of this vaccine on non-mycobacterial infections, cancer and autoimmunity. This interpretative synthesis aims at providing a plausible immunological and immunogenetic model by which BCG vaccination may, in fact, be beneficial for the current efforts in combating COVID-19.
Keywords: immunogenetics; immunology; trained immunity; heterologous immunity; BCG trained immunity; TLR signalling; COVID-19 and BCG